TRANSFORMASI DIGITAL EKONOMI MELALUI KOLABORASI AKADEMISI DALAM MEMBENTUK GENERASI Z KREATIF DI ERA SOCIETY 5.0 - Yessi Avita Sari; Heni Noviarita; Erike Anggraeni (LPPM Universitas Bina Bangsa, 2023)
The digital transformation of the economy in the era of society 5.0 focuses on the strategic role of academics in shaping generation Z creativity through understanding technology and innovation in the digital economy. The implementation location is in Tulang Bawang district, Lampung province. The aim of this service is to prepare generation Z in Tulang Bawang district to face the resistance of Society 5.0. The implementation method is an engaging and courageous lecture accompanied by meaning and practice. Participants in this implementation were 40 IAI (Islamic Religious Institute) Tulang Bawang college students from the Sharia Economics Study Program. Then, there were 40 students in class XII majoring in Social Sciences YPI MA Al-Falaah Banjar Baru. The result of the training is introducing platform technology such as Google Site, Facebook Ads, and Canva. This service has the urgency of technology education and training as well as joint efforts by scientists and generation Z in exploring the potential of the digital economy, which is an important step in preparing for the marketing challenges of the Society 5.0 era